Student-centered Approach in Teaching and Learning: What Does It Really Mean? - Tang, Kuok Ho Daniel (Tecno Scientifica Publisher, 2023)
Student-centered approach has been the center of attention in teaching and learning as the emphasis to shift away from teacher-centered approach is growing. While the term has been widely used, it remains unclear how it can be effectively operationalized given the continuum nature of teacher-centered and student-centered approaches. This article examines 34 articles and included a thematic analysis of their contents to systematically present the methods to operationalize student-centered approach. A channel to practice student-centered approach is project-based learning where students work on projects, such as community and design projects, and are expected to manage the projects or at least propose actions or solutions. Problem-based learning is a variant of project-based learning and students often work on scenarios, cases, questions, or problems which are less extensive than projects. Problem-solving usually precedes lectures to promote self-directed learning and facilitate scaffolding. An argument-based curriculum incorporates arguments and debates that engage students in the self-discovery of different perspectives on a given topic. Student-centered approach is closely linked to the use of technology for research, interactions, gamification, simulations, and feedback. Student-centered feedback prompts active learning through deliberate feedback while adaptive teaching involves students in content-building. This review contributes to the enhancement of student-centered elements in teaching and learning.